Understanding the significance of Olympic values in adults of Chile and Argentina - Tamayo, Alejandro Bacot; Ponciano Nuñez, Pedro Danilo; Giakoni-Ramírez, Frano; Flández-Valderrama, Jorge; Duclos-Bastías, Daniel (International Journal of Evaluation and Research in Education (IJERE), 2024)
Olympic values serve as a significant educational strategy advocated by both the International Olympic Committee and National Olympic Committees globally. Despite their widespread promotion, there exists a dearth of research comparing the comprehension of Olympic values among the adult population. This study aimed to scrutinize the understanding of Olympic values among a sample of 200 Chilean and Argentine adults aged between 18 and 65 years. The investigation was conducted in the context of recent mega sporting events, specifically the Youth Olympic Games in Buenos Aires 2018 and the forthcoming Pan American Games in Santiago 2023. Employing the Fair Play theory and the Moral Competence Test, the research revealed a higher level of moral competence in the Argentine population compared to their Chilean counterparts. Interestingly, no discernible impact of the Youth Olympic Games in Buenos Aires was observed in Argentina. Parental influence emerged as the most significant factor affecting moral competence in both countries, while religion and media demonstrated comparatively less influence. These findings contribute to a more nuanced understanding of the interplay between Olympic values, moral competence, and contextual factors in adult populations across different nations.